Analysis of bacterial foodborne disease outbreaks in Jiangxi Province from 2015 to 2019 - ZENG Liai; LIU Chengwei; YOU Xingyong; XIA Zhilu; TONG Wei; LIU Yang (Zhongguo shipin weisheng zazhi, 2023)
ObjectiveTo provide the scientific basis for control and prevention of bacterial foodborne diseases， the epidemiology characteristics of bacterial foodborne disease outbreaks in Jiangxi Province from 2015 to 2019 were analyzed.MethodsThe descriptive analysis was conducted on the data of bacterial foodborne disease outbreaks in Jiangxi Province reported through “Foodborne Disease Outbreak Reporting System” from 2015 to 2019.ResultsA total of 161 bacterial foodborne disease outbreaks were reported in Jiangxi Province from 2015 to 2019， including 1 682 patients and 794 hospitalizations. The average annual incidence was 0.73/100 000. And the most incidents occurred from May to October. Salmonella and Vibrio parahaemolyticus were the main pathogen factor of bacterial foodborne diseases， and the number of incidents and patients accounted for 45.4% （73/161） and 56.4% （949/1 682） of the total， respectively. Meat and meat products were the main causing food. Families， hotels or restaurants， rural banquets， school and office canteens were the main places of bacterial foodborne disease outbreaks. Improper processing and storage， contamination or spoilage of raw material were the main cause of outbreaks.ConclusionBacterial foodborne diseases is still a major public health problem in Jiangxi Province. In high-incidence seasons， supervision should be targeted at key foods and places， education and training should be targeted at the relevant personnel to strengthen the awareness of family food safety and reduce the occurrence of bacterial foodborne diseases.